Induksi Poliploid Planlet Pisang Kepok Batu Dengan Media Kultur Jaringan - Sabana, Amaliya; Ernawiati, Eti; Priyambodo, Priyambodo; Agustrina, Rochmah (ORGANISMS: JOURNAL OF BIOSCIENCES, 2022)
Colchicine is often used in plant breeding to induce mutations and produce polyploid plants with superior traits. Cytologically polylpoid plants have variations in shape, number of chromosomes and larger cell sizes. The use of colchicine in kepok batu bananas is expected to produce polyploid banana kepok batu plants. The purpose of this study was to determine the effect of colchicine compounds on mitotic abnormalities, changes in chromosome number, decreased mitotic index, and the number and length of roots in banana kepok batu plantlets formed on tissue culture media. The research was carried out at the Botanical Laboratory, Department of Biology, FMIPA Unila. This study compared cytology with the squash method between root tip cells of banana kepok batu plantlets after the addition of 0.1% colchicine with controls. Data were analyzed descriptively and displayed in the form of tables and bar charts. The results showed that administration of 0.1% colchicine resulted in mitotic abnormalities (mitotic abnormalities) and increased the number of chromosomes in the control 2n=3x or 33 and 0.1% colchicine treatment, namely 2n=3x+6 or 39. The mitotic index decreased, but averaged – the average number of roots was more and their size was longer than the control. From these results it can be concluded that the administration of 0.1% colchicine was able to induce polyploid cells in banana kepok batu plantlets.AbstrakKolkisin sering digunakan dalam pemuliaan tanaman untuk menginduksi mutasi dan menghasilkan tanaman poliploid dengan sifat unggul. Secara sitologi tanaman polilpoid memiliki variasi bentuk, jumlah kromosom serta ukuran selnya lebih besar. Penggunaan kolkisin pada pisang kepok batu diharapkan dapat menghasilkan tanaman pisang kepok batu poliploid. Tujuan penelitian ini untuk mengetahui pengaruh senyawa kolkisin terhadap abnormalitas mitosis, perubahan jumlah kromosom, penurunan indeks mitosis, serta jumlah dan panjang akar pada planlet pisang kepok batu yang terbentuk pada media media kultur jaringan. Pelaksanaan penelitian di Laboratorium Botani Jurusan Biologi FMIPA Unila. Penelitian ini membandingkan sitologi dengan metode squash antara sel ujung akar planlet pisang kepok batu setelah penambahan kolkisin 0,1% dengan kontrol. Data dianalisis secara deskriptif dan ditampilkan dalam bentuk tabel serta diagram batang. Hasil penelitian menunjukkan bahwa pemberian kolkisin 0,1% memunculkan kelainan mitosis (abnormalitas mitosis) serta meningkatkan jumlah kromosom pada kontrol 2n=3x atau 33 dan perlakuan kolkisin 0,1% yaitu 2n=3x+6 atau 39. Indeks mitosisnya menurun, namun rata – rata jumlah akar lebih banyak dan ukurannya lebih panjang dibandingkan dengan kontrol. Dari hasil tersebut dapat disimpulkan bahwa pemberian kolkisin 0,1% mampu menginduksi sel – sel poliploid pada planlet pisang kepok batu.